Desenvolvimento de método de quantificação de estatinas em efluente hospitalar e estudo de degradação oxidativa avançada - Altissimo, Joseline (2015)
In this study, an analytical method was developed for the quantification of statins Atorvastatin and Simvastatin, in hospital effluent (University Hospital of Santa Maria, using Solid phase extraction and Dispersive liquid-liquid microextraction, followed in liquid chromatography coupled to diode array detector. The principal variables of Dispersive liquid-liquid microextraction were investigated with aid of experimental central composite design. The recovery rates of Solid phase extraction varied from 95% for Atorvastatin and 83.2% for Simvastatin, in aqueous solution, and 92.0% for Atorvastatin and 81.5% for Simvastatin, in hospital effluent. As for the Dispersive liquid-liquid microextraction the recovery rates ranged from 85.5% for Atorvastatin and 89.4% for Simvastatin, in aqueous solution, and 83.0% for Atorvastatin and 83.1% for Simvastatin, in hospital effluent. The sampling was carried out in two sample points called Emergency Effluent and General Effluent . The concentration rates detected in the effluent were 30.1 μg L-1 in Emergency Effluent and 29.0 μg L-1 in General Effluent for Atorvastatin and 37.1 μg L-1 in Emergency Effluent and 36.1 μg L-1 in GE for Simvastatin. Ozonation and electrocoagulation were applied for the degradation/removal of statins. The principal variables of electrocoagulation were investigated with aid of experimental central composite design. The degradation rate obtained in ozonation was 100% for Atorvastatin, in 25 minutes reaction for aqueous solution and hospital effluent; and 100% for Simvastatin, in 4 minutes reaction for aqueous solution and 10 minutes reaction in hospital effluent. As for the electrocoagulation the removal rate was 75.6% in aqueous solution and 70.9% in hospital effluent for Atorvastatin; and 100% in aqueous solution and hospital effluent for Simvastatin in 60 minutes reaction. A preliminary risk evaluation revealed that the statins showed a low environmental risk, PEC/PNEC < 1.